DEPENDENCY FORECASTING IN THE DISTRIBUTED AGILE ORGANIZATION. - WAGSTROM, PATRICK; HERBSLEB, JAMES (Communications of the ACM, 2006)
The article focuses on task coordination in globally distributed system development (GDSD). The authors argue that agile project management of GDSD is challenging. Constant communications is a necessity especially in projects that have a long duration or involve many software developers. The authors describe an automated method in order to determine who should be included in communications on specific aspects of a project. Instead of relying on project management staff to constantly redraw communications "maps," the authors propose an automated process that examines who is working on specific areas of the software's code.